Makna semantik kerja perintah Bahasa Arab, peranannya dalam ilmu Usul al-Fiqh dan implikasinya terhadap pengajaran dan pembelajaran Bahasa Arab - Sahrir, Muhammad Sabri; Ibrahim, Ahmad Basri; Abd Rahman, Ghazali Yusri (2011)
This paper highlights a variety of meanings and usage of the imperative verb in Arabic semantic and its signifance in the discipline of Usul al-Fiqh (Islamic Jurisprudence). It begins with the definitions of Arabic imperative verb as defined by the scholars of linguistics and the Quranic interpretors as well. The study discovers that there is a variety of literal and contextual meanings of Arabic imperative verb that can be found from the Quranic verses, the Sunnah of the Prophet P.B.U.H. and Arabic poems as discussed by the Quranic interpretors, the Sunnah commentators as well as the scholars of linguistics. As a matter of fact, this factor contributes to the derivation of different Islamic legal rulings from their sources even though they are acquired from the same Arabic imperative verb. Thus, it is crucial to the Mujtahid or Muslim jurist to understand the nature and the practical application of Arabic imperative verb in deriving Islamic legal rules from their sources which are primarily in Arabic. In addition, this paper presents the beauty of Arabic language that is chosen by Allah to be the language of the Holy Quran, as the main guidance for the whole mankind and the implication of this study towards the teaching and learning Arabic.